Bir eser-i siyâsî - Mustafa Fâzıl Paşa, 1830-1875. (Dersaâdet [İstanbul] [y.y.] İstanbul İstanbul Dersaâdet Dersaâdet Dersaâdet [İstanbul] İstanbul, 1911)
10 kitap 1 ciltte (27 s. ; 32 s. ; 46 s. ; 21 s. ; 58, [1] s. ; 23 s. ; 30 s. ; 92 s. ; [1], 47 s. ; 32 s.)